Development of a new in-home testing method to assess infant food liking. (1st June 2017) - Madrelle, J.; Lange, C.; Boutrolle, I.; Valade, O.; Weenen, H.; Monnery-Patris, S.; Issanchou, S.; Nicklaus, S.
Abstract: The objective of this study was to develop a new elaborate method to evaluate infants' liking of foods that could be applied at home and to compare the results of this elaborate method with those of a basic method. Mothers of infants aged 4 to 7 (n = 44) and 12–15 months (n = 46) participated in this study. For the basic method, mothers were asked to assess their infant's global liking at the end of a meal. Then, for the elaborate method, mothers received detailed instructions on how to feed their infant, how infants might express like/dislike and when to stop the meal. During the first nine spoons, they were asked to report the presence/absence of positive and negative behaviours after each spoon, and the infant's initial liking was reported after each triplet of spoons. They also assessed their infant's global liking at the end of the meal. Both methods were applied using three commercial familiar baby foods adapted to each age range. In 4-7-month-olds, the elaborate method showed a significant difference across products for liking, whereas the basic method did not show any difference. In 12-15-month-olds, the elaborate method showed more differences across products for liking than the basic method. In both age groups, negative behaviours, despite being less frequently reported, provided better liking discrimination than positive behaviours. In conclusion, the elaborate method produced better product liking discrimination than the basic method by focusing maternal attention on infants' eating behaviours since the first spoons.